A Clean Sweep? : The Politics of Ethnic Cleansing in Western Poland, 1945-1960 - Curp, T. David, 1965- (Book collections on Project MUSE., 2006)
A Clean Sweep? The Politics of Ethnic Cleansing in Western Poland, 1945-1960' examines the long-term impact of ethnic cleansing on postwar Poland, focusing on the western Polish provinces of Poznan and Zielona Góra. Employing archival materials from multi.